Theology of law - GAŁKOWSKI, TOMASZ (Prawo Kanoniczne, 2013)
The beginnings of theology of law should be sought in the Protestant theology during the prevalence of Nazi ideology. On the Catholic ground, the theology of law as it was developed in Protestantism gained the character of theology of the Canon Law or was blurred as part of moral theology in which the reference point for the assessment of law was lex moralis naturalis. Theology of law from the Catholic point of view should abandon deliberations on the moral aspect of the norm and assume as a starting point the categorical, intersubjective and obligatory relation as an object of research. Therefore, theological-legal interests should focus on the human himself who creates the relation of obligation and fills it with meaning. Telling about the one who is the author of the legal relation in the light of Revelation, theology of law points out the foundations of a legal phenomenon. Thus, theology of law refers to the law itself in the light of Revelation, framing its theological foundations. If the theology of law concentrated solely on the aspect of content of the legal relation (the norm) or wished to favour it in comparison with the interpersonal relation itself, it would make law a static reality, expressed by a human as a certain form of explicit way of existence and activity. Theology of law plays a vital role on the epistemological plane learning about a human living sub specie iuris. In this respect, theology of law has a tremendous role to play in the cultural and legal context as a specific hermeneutic category in getting familiar with and understanding a legal relation. Theology of law can give law new horizons of its existence and reveal a new sense to it. The objective of theology of law is not filling law with theological content but showing it the realities discovered in a different way of cognition. Theology of law can become a cognitive suggestion and inspiration for the established law.